Politics of New Labour, The : A Gramscian Analysis - Pearmain, Andrew (Book collections on Project MUSE., 2014)
This book is an attempt 'to think in a Gramscian way' about the curious political phenomenon of New Labour. It is written partly in retort to those people at the heart of the New Labour project who have cited Gramsci as a source of inspiration for their ideas. Pearmain argues that New Labour makes a far better object than agent of Gramscian analysis.